2021
DOI: 10.3390/foods10030641
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Metabolite Profiling and Microbial Communities of Doenjang (Fermented Soy Paste) and Ganjang (Fermented Soy Sauce): A Comparative Study

Abstract: Doenjang and ganjang are secondary fermented soybean products from meju (primary fermented product) following a complex fermentation process that separates the products into solid (doenjang) and liquid (ganjang) states. We performed a comparative study on gas chromatography mass spectrometry-(GC-MS) and liquid chromatography mass spectrometry-(LC-MS) based metabolite profiling with fungal and bacterial microbial community analysis of doenjang and ganjang during fermentation. Metabolite profiling and microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Enterobacter, Bacillus and Millerozyma genus also had strongly positively correlation with total phenols, total flavonoids and five monomer flavonoids, while Enterococcus, Staphylococcus, Rhizopus and Aspergillus genus showed negative correlation. This indicated that Bacillus and Millerozyma genus might be the main microbes involved in the formation of AAs and biologically active compounds in doubanjiang, while organic acids were produced by different bacterial and fungal genus, which was in consistent with previous researches[38,39].…”
supporting
confidence: 90%
“…Enterobacter, Bacillus and Millerozyma genus also had strongly positively correlation with total phenols, total flavonoids and five monomer flavonoids, while Enterococcus, Staphylococcus, Rhizopus and Aspergillus genus showed negative correlation. This indicated that Bacillus and Millerozyma genus might be the main microbes involved in the formation of AAs and biologically active compounds in doubanjiang, while organic acids were produced by different bacterial and fungal genus, which was in consistent with previous researches[38,39].…”
supporting
confidence: 90%
“…Although the fungi community was not determined, the different contents of bioamine indicated the different fungi community in TMK. Interestingly, the predominant bacteria in some TMK (HBHB and HBLB) were Bacillus subtillus, similar to doenjang and chungkookjang, but some were not [35]. On the other hand, those in LBHB and LBLB included small portions of the present study.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, those in LBHB and LBLB included small portions of the present study. A few studies have been conducted for TMK by NGS: predominant bacteria in TMK are Staphyloccocus and Tetragenococcus, and TMK contains low Bacillus [35]. It suggests that different TMK contains different bacteria communities, and large-scale studies need to be conducted to explore the bacteria community for TMK.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported members of the genera Weissella , Leuconostoc, Lactobacillus , Streptococcus, Enterococcus , Lactococcus and Pediococcus as dominant lactic acid bacteria in fermented foods [ 30 , 31 , 32 , 33 ]. This was expected since all products exhibited a pH of around 3.5 to 4.6.…”
Section: Resultsmentioning
confidence: 99%